Serum Protein Alterations In Malignant Neoplasia - SUDHA K; GAYA PR; CHARU YADAV (International Journal of Pharma and Bio Sciences, 2015)
Malignant neoplasia is thought to develop through multifactorial gene stimulations which leads to marked variations in plasma proteins. The study aims at the quantification of serum albumin and different globulin fractions in 28 multiple myeloma and 25 other hematological cancer and compare the alterations with that of 40 age and sex matched normal subjects. Serum albumin and total proteins were estimated by spectrophotometric methods. Quantitation of globulin fractions were done by scanning the electrophoretogram by densitometry. Hypoalbuminemia and hypergammaglobulinemia were evident both in multiple myeloma and leukemia compared to normal from the results of the present study. Further, decrease in albumin was statistically significant in leukemia compared to multiple myeloma. While α1globulins increased in leukemia, β globulins increased significantly in multiple myeloma compared to normal .The results provide evidence to support the idea that different type of globulins increase in varied types of hematological cancers. Further work needs to be carried out to allow us to understand the underlying mechanisms that has led to the increase of α1 or β globulins in hematological cancers and explore new tumor markers.